ISOLASI SENYAWA AKTIF “BRINE SHRIMPS“ AKAR Garcinia cowa Roxb FRAKSI ETIL ASETAT - afdhil arel (Jurnal Ipteks Terapan, 2015)
AbstractFlavonoid compound has been isolated as yellow crystalline which has melting point at 218-220˚C from root of Garcinia cowa Roxb. The compound was isolated by using column chromatography and characteristic with ultra violet spectroscopy, infrared spectroscopy, mass, 1H-NMR, and 13C-NMR.   The indicated this compound was hegoflavon (B). Anticancer activities of aethyl acetat fraction and hegoflavon (B) using “Brine Shrimps“ gave LC50 37,325 µg/ml and 1,95 µg/ml.